MANAJEMEN KEMITRAAN DI LEMBAGA PAUD (Studi Multi Situs TK Negeri Pembina Banjarmasin Tengah dan TK Negeri Pembina Banjarmasin Timur) - Mustika Nur Oktaviani; Aslamiah; Effendi, Rustam; Suriansyah , Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze partnership management in early childhood education institutions (PAUD) through a multi-site study conducted at TK Negeri Pembina Banjarmasin Tengah and TK Negeri Pembina Banjarmasin Timur. The research explores partnership management in PAUD institutions through three main focuses: (1) the leadership of the PAUD principal in managing partnership programs, (2) the principal’s communication in establishing partnerships, and (3) the principal’s strategies in building a culture of collaboration. This study employs a qualitative approach using a multi-site case study method. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using the Miles and Huberman model. The results indicate that the principals at both TK Negeri Pembina Banjarmasin Tengah and TK Negeri Pembina Banjarmasin Timur demonstrated collaborative, participative, and communicative leadership in designing and implementing partnership programs. The institutions’ vision and mission served as the foundation for all partnership activities and were developed democratically by involving all stakeholders. In terms of communication, the principals established open, adaptive, and sustainable two-way communication through various formal and informal channels. This approach strengthened trust and active participation from parents and external partners, enhancing synergy in supporting school programs. Meanwhile, the strategy for building a collaborative culture was implemented by fostering an inclusive atmosphere, establishing mutual trust in partnerships, and expanding networks of cooperation with external institutions. These strategies effectively nurtured a sense of ownership, increased stakeholder involvement, and created a sustainable collaborative culture to support the holistic quality of early childhood education services. The study concludes that the success of partnership management in PAUD institutions highly depends on effective school leadership, harmonious communication, and a structured collaborative culture. This research contributes to the development of partnership management practices as an effort to improve the quality of early childhood education. Keywords: Partnership Management, Early Childhood Education, School Leadership, Communication, Collaborative Culture.